2021
DOI: 10.1371/journal.pone.0245136
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health as a mediator between physical health conditions and depressive symptoms in older Chinese and Korean Americans

Abstract: In the present study, we examined self-rated health as a mediator between physical health conditions (chronic diseases and functional disability) and depressive symptoms in older Chinese and Korean Americans. Using harmonized data (N = 5,063) from the Population Study of Chinese Elderly (PINE) and the Study of Older Korean Americans (SOKA), we tested direct and indirect effect models. In both groups, chronic diseases and functional disability were closely associated with negative ratings of health and symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
(60 reference statements)
1
10
0
1
Order By: Relevance
“…This finding supports the previous studies that highlighted that low self-rated health was a strong and consistent predictor of risk for depressive symptoms (21,57). With the presence of chronic diseases and functional disability could also make people prone to negatively perceived their health and experienced symptoms of depression (58).…”
Section: Discussionsupporting
confidence: 90%
“…This finding supports the previous studies that highlighted that low self-rated health was a strong and consistent predictor of risk for depressive symptoms (21,57). With the presence of chronic diseases and functional disability could also make people prone to negatively perceived their health and experienced symptoms of depression (58).…”
Section: Discussionsupporting
confidence: 90%
“…This investigation was prompted by multiple causes, including the increase in the older Asian immigrant population in the U.S. (Hanna & Batalova, 2021; U.S. Census Bureau, 2019), public health concerns about immigrant health and language barriers (Lommel & Chen, 2016; Tan & Burgess, 2020), increased attention to brain aging and cognitive health in older immigrants (Lamar et al, 2021; Xu et al, 2017), lack of appropriate data on older Asian Americans (Đoàn et al, 2019), and the potential of merging the datasets for older Chinese and Korean Americans (Jang et al, 2021). Harmonized data from two independently designed studies (the PINE and SOKA), which employed culturally and linguistically sensitive approaches to reach out to older Chinese and Korean Americans, generated a combined sample size of 5063 and allowed us to examine between- and within-group differences in the association between linguistic adaptation and cognitive function at a cross-sectional level.…”
Section: Discussionmentioning
confidence: 99%
“…These inconclusive findings are attributable in part to the use of varied measures of acculturation, including proxies (e.g., nativity, age at migration, length of residence in the U.S.) and scales with multiple domains of cultural adaptation (e.g., language, media use, food consumption, social relationships, familiarity with customs and practices); hence, in the present study, we focus on linguistic adaptation, which is the most integral component of acculturation (Lommel & Chen, 2016; Tan & Burgess, 2020). Such a targeted approach is also imperative for harmonizing data from independently designed studies with different measures in order to optimize those data for comparability (Jang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies had revealed that the number of chronic conditions had a strong association with self-rated health among older people ( 26 , 30 ). Furthermore, a study conducted among older Chinese and older Korean Americans indicated that self-rated health played a mediating role between chronic conditions and depressive symptoms in both groups ( 31 ). Thus, self-rated health might be a mediator in the relationship between chronic conditions and PD in this study.…”
Section: Introductionmentioning
confidence: 99%